Müasir Azərbaycan mədəniyyətinin qurucusu - Seyfullayeva Aynur Tahir qızı (Academics and Science Reviews Materials, 2023)
Azerbaijan is known in the world for its culture, art, national-spiritual values. The roots of the national and moral values of our people go back to ancient times. In the 20th century, a new era began in the cultural life of our people. This is a period associated with the name of the great leader Heydar Aliyev. The great leader said that "the nation is recognized and recognized for its many characteristics and stands out among the nations of the world. The highest and greatest of these features is culture." That is why the great leader always focused on the development of the people’s culture during all the periods he was in power.